Configuration of the Volatile Aromatic Profile of Carob Powder Milled From Pods of Genetic Variants Harvested at Progressive Stages of Ripening From High and Low Altitudes - Antoniou, Chrystalla; Kyratzis, Angelos C.; Soteriou, Georgios A.; Rouphael, Youssef; Kyriacou, Marios C. (Frontiers in Nutrition, 2021)
Carob powder is increasingly valued as a substitute for cocoa and as a flavor-enhancing component of processed foods. However, little is known about the impact of preharvest factors such as fruit maturity, genotype and altitude on its volatile organic compounds (VOCs) composition. The current study examined the VOCs composition of powder milled from pods of two genotypes cultivated at 15 and 510 m altitude and harvested at six progressive stages of maturity, ranging from fully developed immature green (RS1) to late ripe (RS6). Fifty-six VOCs categorized into acids, esters, aldehydes, ketones, alcohols, furans, and alkanes were identified through HS-SPME GC-MS analysis. Maturity was the most influential factor, followed by altitude and least by genotype. Aldehydes and alcohols correlated positively (r = 0.789; p < 0.001), both accumulated in immature carobs and decreased with progressive ripening, resulting in the attenuation of green grassy aroma. Conversely, acids increased with ripening and dominated the carob volatilome at full maturity, correlating negatively with aldehydes and alcohols (r = −0.835 and r = −0.950, respectively; p < 0.001). The most abundant VOC throughout ripening (17.3-57.7%) was isobutyric acid, responsible for the characteristic cheesy-acidic-buttery aroma of carob powder. The pleasurable aroma detected at the immature stages (RS2 and RS3) was traced to isobutyrate and methyl isobutyrate esters, rendering unripe green carob powder a potential admixture component for improving the aroma of novel food products. Lower altitude favored the accumulation of acids linked to less pleasant aroma, whereas isobutyric acid was more abundant at higher altitude. This constitutes a significant indication that higher altitude enhances the characteristic carob-like aroma and sensory quality of carob powder.